Beyond yield: Unveiling farmer perceptions and needs regarding weed management in Bangladesh - Islam, Md Mirajul; Rahman, Md Mizanur; Sarker, Shashanka Shekhar; Islam, Md Nazrul; Bhuiyan, Fahmid H.; Khanam, Mst Salma; Alam, Iftekhar (Frontiers in Bioengineering and Biotechnology, 2024)
More than 3.5 billion people depend on rice for more than 20% of their daily calories. Globally, Bangladesh is the third largest rice producer. With 171 million people, Bangladesh is also among the top consumers. Local rice production not only affects its food security but also influences the global rice trade. A large yield gap has been reported due to weeds. Traditional hand-weeding is very costly because of labor shortages resulting from industrialization. Limited data showed a higher yield and profits when using herbicides. However, quantitative data lacks various aspects of weed management and associated issues representing the country's variable rice ecosystem characterized by 30 agroecological zones. We collected data on weed management practices from 865 farmers and 69 agrochemical shops covering all 30 AEZs through a structured survey. We observed a significant regional variation among various parameters. About 82% of farmers use herbicides, while they rarely rely solely on manual weeding or herbicides. Pre-emergence herbicides are the predominant.Application procedures are almost the same across the country. Although 40% of farmers had secondary and higher-level education, most depend upon local sellers' suggestions rather than reading the product label regarding the dose. Few farmers consider herbicides hazardous, and respondents rarely perceive any environmental impact. Pyrazosulfuron-ethyl (35%) and acetochlorcontaining bensulfuron-methyl (27%) are the most used chemical species. About 45% of farmers observed that herbicide suppresses early seedling growth. Additional fertilizer is required to compensate for this. In all AEZs, multiple weed species are noticed, which are difficult to control through presently used herbicides. Around 64% of farmers observed that herbicide application contributes to higher yields as a function of timely weeding. Cost comparison showed that high labor prices will make rice cropping unprofitable in most parts of the country if herbicides are eliminated.Clear adverse effects of pre-emergence herbicides on early crop growth implied the potential benefits of broad-spectrum herbicide-tolerant genetically engineered rice to sustain the country's food security. Additionally, such GE rice could incentivize the adoption of alternate wet and dry irrigation methods, leading to water and cost savings.